Modeling of kenaf reinforced sugar palm starch biocomposites mechanical behaviour using Halpin-Tsai model - Mansor, Muhd Ridzuan; Salit, Mohd Sapuan; Salim, M. A.; Akop, Mohd Zaid; Tahir, M. M. (WSEAS Press, 2015)
This paper presents the application of theoretical modeling approach in studying the mechanical behaviour of kenaf reinforced sugar palm starch (SPS) biocomposites. Kenaf reinforced SPS is new class of biocomposites that offered high specific mechanical property and fully biodegradable and renewable properties which is very promising for eco-friendly product applications. Halpin-Tsai micromechanical model was employed to model the final biocomposites elastic modulus behaviour in both varying fiber contents and varying fiber length conditions. The kenaf fiber contents were varied from 0 to 50 wt% where as the fiber length was varied from 1 mm to 3 mm. Modeling results showed that elastic modulus for final kenaf reinforced SPS biocomposites increased as the total kenaf fiber contents were increased, for both longitudinal and transverse direction. Apart from that, increased in kenaf fiber length was also shown to effect higher elastic modulus of the due to increase in the reinforcement aspect ratio. The Halpin-Tsai model implemented in this study also proved its suitability for preliminary biocomposites design purpose in order to gain quick and cost effective information prior to experimental biocomposites characterization approach.